Control study of low tube voltage computed tomography angiography (CTA) and digital subtraction angiography (DSA) in diagnosing intracranial micro‐aneurysm. Issue 2 (28th November 2017) - Li, Rui; Duan, Yuxia; Liu, Jinjin; Cao, Guoquan; Yang, Yunjun; Zhuge, Qichuan; Chen, Weijian
Abstract: The aim of this study was to investigate the diagnostic values of low tube voltage cerebral computed tomography (CT) angiography (L‐CTA, 100 kV) of intracranial micro‐aneurysms (IMA, maximum diameter ≤3 mm). The clinical and imaging data of a total of 59 IMA patients confirmed by 3D rotational angiography (3DRA) or surgery were retrospectively analyzed; their L‐CTA data were compared with those of IMA and 3DRA so as to investigate the diagnostic sensitivity, specificity, and accuracy of IMA, as well as to objectively evaluate the related radiation dose. Based on the results of 3DRA, 65 cases of IMA and a total of 70 aneurysms, including 65 micro‐aneurysms, were found in the 59 cases. L‐CTA detected a total of 64 IMA, including six multiple cases of IMA, as well as three false positive cases and four missed cases. Compared with the 3DRA (gold standard), the diagnostic sensitivity, specificity, and accuracy of L‐CTA toward IMA were 93.85%, 99.56%, and 99.08%, respectively, and the associations of aneurysm size measured by L‐CTA and 3DRA were good. Compared with conventional CTA, the effective dose of L‐CTA was reduced by 36.23%. L‐CTA has high diagnostic sensitivity toward IMA, and can effectively reduce the radiation dose, so it is worth implementing.